Human resource planning strategy to improve employee performance in facing the industrial revolution 4.0 - Prabowo, Satria Agung; Prasetiyo, Arditiya Bayu; Prasetya, Arief Budi; Supratikta, Hadi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study was prompted by a change in business policy that substituted human labor with machine labor, as a result of increasingly advanced technology breakthroughs. One option is to develop a Human Resources planning strategy for the period of Industrial Revolution 4.0, so that employees are not defeated by machines in the future. The problem formulation in this study is,